2012
DOI: 10.12693/aphyspola.121.666
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Switching Properties of InGaSe2Single Crystal

Abstract: The goal of this paper is to present experimental results of the switching eect and analyze qualitatively the inuence of various factors, such as temperature, light illumination and sample thickness on switching behavior of the high quality ternary chalcogenide semiconductor InGaSe2. Current-controlled negative resistance of InGaSe2 single crystals has been observed for the rst time. It has been found that indium gallium diselenide single crystals exhibit bistable or memory switching. The switching process tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In recent years, it has been observed that the switching effect is not only characteristic of these kind of materials but is also present in many crystalline materials, like binary semiconductor and ternary chalcogenide semiconductor compounds such as TlGaTe 2 , TlInSe 2 , TlInTe 2 and InGaSe 2 . [19][20][21][22] The switching effect plays an important role in technological applications such as information storage, power control devices, thermistors, oscillators, etc. 23 In this work, we present measurements of the electrical conductivity of TlBiSe 2 ternary crystals in the temperature range from 293 K to 373 K, and investigate the dominant conduction mechanism in the preswitching state of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been observed that the switching effect is not only characteristic of these kind of materials but is also present in many crystalline materials, like binary semiconductor and ternary chalcogenide semiconductor compounds such as TlGaTe 2 , TlInSe 2 , TlInTe 2 and InGaSe 2 . [19][20][21][22] The switching effect plays an important role in technological applications such as information storage, power control devices, thermistors, oscillators, etc. 23 In this work, we present measurements of the electrical conductivity of TlBiSe 2 ternary crystals in the temperature range from 293 K to 373 K, and investigate the dominant conduction mechanism in the preswitching state of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the present sonochemicalm ethod is more efficient than the solvothermal preparation of InSe at 180 8C. [20] The (In 0.68 Ga 0.32 )Se 1.81 (In-Ga-Se) powder showed an XRD pattern that wass imilar to that of the In 1.00 Se 1.86 precursor,i ndexed as the cubic or tetragonal structure [21,22] because of the broad peak near 2 q = 448.T he sonochemical synthesis incorporated gallium in the pristine InSe lattice and randomly distributed indium and gallium in the metal sites. The final product, Cu 1.00 (In 0.68 Ga 0.30 )Se 2.01 ,a lso exhibited approximately 90 % yield on the basis of the metalsa nd as maller cubic cell [a = 5.644(4) ] than In 1.00 Se 1.86 .U pon incorporation of Cu + and Ga 3 + cations,w hich have smaller ionic radii than In 3 + (Cu + : 91 pm, Ga 3 + :76pm, In 3 + :94pm), into the zincblende In-Se lattice, the bond length between the cation and anion decreased and the unit cell shrank.…”
Section: Resultsmentioning
confidence: 76%
“…The poor solubility of selenium strongly influenced the crystal structures of InSe, that is, hexagonal and cubic struc- (2) [a] The lattice parameters were calculated by least-square refinements. [20] The (In 0.68 Ga 0.32 )Se 1.81 (In-Ga-Se) powder showed an XRD pattern that wass imilar to that of the In 1.00 Se 1.86 precursor,i ndexed as the cubic or tetragonal structure [21,22] because of the broad peak near 2 q = 448.T he sonochemical synthesis incorporated gallium in the pristine InSe lattice and randomly distributed indium and gallium in the metal sites. [19] Dissolutiono fs eleniumat1 10 8Cb yultrasound treatment produced cubic-phase InSe.…”
Section: Resultsmentioning
confidence: 91%
“…We can also observe that TlInSeS is a quaternary semiconductor exhibiting S-type I-V characteristics, similar to the curves shown by many authors. [13][14][15][16][17][18] 3.2 Temperature dependence of I-V characteristics The temperature dependence of the I-V characteristics is an important factor in choosing a switching material for an information-storage application. In the present study, the effect of the temperature on the I-V characteristics and the switching behaviour of the TlInSeS compound have been investigated in the temperature range from 173 to 303 K under static conditions, as shown in Fig.…”
Section: Current-controlled Negative Resistance (Ccnr) Withmentioning
confidence: 99%